Answer:
True.
Step-by-step explanation:
The sides of a triangle rule asserts that the sum of the lengths of any two sides of a triangle has to be greater than the length of the third side. this makes it possible for the triangle to be formed.
Answer: -13/17
Step-by-step explanation:
Answer:
1) (n+5)(n-1)
2) (n-4)(n+3)
3) (v-4)(v-1)
4) (p-4)(p+2)
5)(7x-10)(x+1)
6)(7n-1)(n-9)
Step-by-step explanation:
1) Factors of -5 that add up to 4
2) Factors of --12 that add up to -1
3) Factors of 4 that add up to -5
4) Factors of -5 that add up to 4
5) 7
-3x-10
7
+7x-10x-10
7x(x+1)-10(x+1)
(7x-10)(x+1)
6)7
-64n+9
7
-63n-n+9
7n(n-9)-(n-9)
(7n-1)(n-9)
Answer:
4 . The answer is no .
5 . x=1
6. unlimited answers
7. There's no answer to this question .
Step-by-step explanation:
___________________
4. solution :
-20(2-4) = 2((5×-4) -4) =
-40 = -48 × impossible
___________________
5. solution :
-3+4x+12x+24 = 28x +12-3
-3+24-12+3=28x-12x-4x
27-15=12 = 2x - 16x =12x
12 = 12x
x =1
__________________
6. solution :
24-3x+9-6 = -8x+20+5x+7
8x-5x-3x = -24-9+6+20+7
0=0
x can be every number you think because they are always equal to each other .
examination :
if you consider x as 1 :
24-3+9-6=-8+20+5+7
24=24
or if you consider x as 2 :
24-6+9-6 = -16+20+10+7
21 = 21
__________________
7 . solution :
3(x-2) = 3x+4
3x-6 = 3x+4
3x-3x = 10
0 = 10
if you consider x as 1 :
3-6 = 3+4
-3 = 7 × impossible .